Short-Circuit Analysis of the Saparua Distribution Feeder Network - Mbitu, Elisabeth Tansiana; Jamlaay, Marselin; Sahusilawane, Ferdiaztha Rendy (Publisher Cv. Inara, 2025)
Short-circuit faults are a type of disturbance that impedes the transmission of electrical energy. To protect equipment from the impact of such faults, short-circuit analysis is conducted. In this study, the magnitudes of phase-to-phase and phase-to-ground short-circuit currents are calculated, along with the determination of overcurrent relay and circuit breaker ratings on the distribution network of PT PLN Saparua Rayon, Maluku. The analysis is carried out using ETAP software on generator busbars and feeders at various fault locations. PT PLN (Persero) Saparua Rayon operates four feeders: Saparua, Pohar, Tenggara (Southeast), and Hatawano. Simulation results show that the Saparua feeder has the highest fault current at bus 6 under an L-L-G fault condition, while the Tenggara, Hatawano, and Pohar feeders exhibit their highest fault currents at the generator bus under an L-G fault. It is evident that the L-L-G (double line-to-ground) fault consistently generates the highest short-circuit current when compared to other types of faults such as L-L (line-to-line) and three-phase faults. This type of fault involves a direct connection between two phases and the ground, resulting in a larger fault current due to lower overall impedance at the fault point. Furthermore, it was observed that the magnitude of the short-circuit current decreases progressively with increasing distance from the power source. This behavior is primarily due to the increase in line impedance along the distribution path, which naturally limits the fault current as it travels farther from the generation point. In summary, the farther the location of the fault from the generator, the lower the resulting short-circuit current, which highlights the critical role of impedance in fault current behavior across the distribution network.